Difference between revisions of "2005 Alabama ARML TST Problems/Problem 7"

(Solution)
 
(One intermediate revision by one other user not shown)
Line 8: Line 8:
 
We can compute those sums:
 
We can compute those sums:
  
<math>\begin{eqnarray}
+
<cmath>\begin{eqnarray*}
 
\sum_{n=1}^{\infty} \left(\frac{3}{2^n}\right)=x\\
 
\sum_{n=1}^{\infty} \left(\frac{3}{2^n}\right)=x\\
 
=3\left(\frac{1}{2}+\frac{1}{4}+\frac{1}{8}+\cdots\right)\\
 
=3\left(\frac{1}{2}+\frac{1}{4}+\frac{1}{8}+\cdots\right)\\
Line 24: Line 24:
 
z=4+\frac{2}{2}+\frac{2}{4}+\frac{2}{8}+\cdots=6\\
 
z=4+\frac{2}{2}+\frac{2}{4}+\frac{2}{8}+\cdots=6\\
 
3+4+6=\boxed{13}
 
3+4+6=\boxed{13}
\end{eqnarray}</math>
+
\end{eqnarray*}</cmath>
 +
 
 +
If you didn't understand the third case / summation, all they did was subtract the summation for <math>z</math> from <math>2z</math> to get the new <math>z</math> and then repeat this.
  
 
==See Also==
 
==See Also==

Latest revision as of 21:13, 18 May 2021

Problem

Find the sum of the infinite series:

$3+\frac{11}4+\frac 94 + \cdots + \frac{n^2+2n+3}{2^n}+\cdots$.

Solution

$\sum_{n=1}^{\infty} \frac{n^2+2n+3}{2^n}=\sum_{n=1}^{\infty} \left(\frac{n^2}{2^n}\right)+\sum_{n=1}^{\infty} \left(\frac{2n}{2^n}\right)+\sum_{n=1}^{\infty} \left(\frac{3}{2^n}\right)$

We can compute those sums:

\begin{eqnarray*} \sum_{n=1}^{\infty} \left(\frac{3}{2^n}\right)=x\\ =3\left(\frac{1}{2}+\frac{1}{4}+\frac{1}{8}+\cdots\right)\\ 2x=3\left(1+\frac{1}{2}+\frac{1}{4}+\frac{1}{8}+\cdots\right)\\ x=3(1)=3\\ \sum_{n=1}^{\infty} \left(\frac{2n}{2^n}\right)=y\\ =\frac{2}{2}+\frac{4}{4}+\frac{6}{8}+\frac{8}{16}+\cdots\\ 2y=2+\frac{4}{2}+\frac{6}{4}+\frac{8}{8}+\cdots\\ y=2+\frac{2}{2}+\frac{2}{4}+\frac{2}{8}+\cdots=4\\ \sum_{n=1}^{\infty} \left(\frac{n^2}{2^n}\right)=z\\ =\frac{1}{2}+\frac{4}{4}+\frac{9}{8}+\frac{16}{16}+\cdots\\ 2z=1+\frac{4}{2}+\frac{9}{4}+\frac{16}{8}+\cdots\\ z=1+\frac{3}{2}+\frac{5}{4}+\frac{7}{8}+\frac{9}{16}+\cdots\\ 2z=2+3+\frac{5}{2}+\frac{7}{4}+\frac{9}{8}+\cdots\\ z=4+\frac{2}{2}+\frac{2}{4}+\frac{2}{8}+\cdots=6\\ 3+4+6=\boxed{13} \end{eqnarray*}

If you didn't understand the third case / summation, all they did was subtract the summation for $z$ from $2z$ to get the new $z$ and then repeat this.

See Also

2005 Alabama ARML TST (Problems)
Preceded by:
Problem 6
Followed by:
Problem 8
1 2 3 4 5 6 7 8 9 10 11 12 13 14 15
Invalid username
Login to AoPS